Pemberdayaan Masyarakat Sebagai Duta Demam Berdarah Untuk Mencapai Sustainable Development Goals Ketiga, Kehidupan Sehat dan Sejahtera - Dewa Ayu Putri Sri Masyeni (Scopus ID: 56160618900); Saraswati Laksmi Dewi; Niti Widari (Community Service Journal (CSJ), 2026)
Background: Dengue infection remains a global health threat in tropical countries. The number of dengue cases fluctuates and continues to increase, with a relatively high mortality rate. This community service aims to provide Dengue Fever Ambassadors among restaurant employee group partners, who will educate other community groups about dengue fever and its prevention. Methods: This community service method involved socialising activities through focus group discussions, delivering counselling materials, conducting training, evaluation, and mentoring, which was done in December 2024. Results: The PKM shows a 70% increase in partner knowledge, observed across all partners, based on pre- and post-test results. The service assessment was conducted over three months and has shown behavioural changes in dengue prevention. Conclusion: Empowering the community is key to managing dengue effectively. Sustainable community education is necessary to enhance the community's knowledge and behaviour to reduce dengue incidence.